Nanobubbles Adsorption and Its Role in Enhancing Fine Argentite Flotation - Shunde Yan; Xihui Fang; Guanfei Zhao; Tingsheng Qiu; Kaiwei Ding (Molecules)
The efficient recovery of fine argentite from polymetallic lead–zinc (Pb–Zn) sulfide ore is challenging. This study investigated nanobubble (NB) adsorption on the argentite surface and its role in enhancing fine argentite flotation using various analytical techniques, including contact angle measurements, adsorption capacity analysis, infrared spectroscopy, zeta potential measurements, turbidity tests, microscopic imaging, scanning electron microscopy, and flotation experiments. Results indicated that the NBs exhibited long-term stability and were adsorbed onto the argentite surface, thereby enhancing surface hydrophobicity, reducing electrostatic repulsion between fine argentite particles, and promoting particle agglomeration. Furthermore, the NBs formed a thin film on the argentite surface, which decreased the adsorption of sodium diethyldithiocarbamate. Microflotation tests confirmed that the introduction of NBs considerably enhanced the recovery of argentite using flotation technology.